Supply and demand flow patterns and optimization of food ecosystem services in China’s Yangtze River Delta - Qiu, Xiaoling; Wang, Xinmei; Wang, Zeni; He, Wei (Frontiers in Sustainable Food Systems, 2025)
Clarifying the relationship between the supply and demand of food ecosystem services and portraying the pattern of supply and demand flows are significant for regional ecological management and food security. The minimum cumulative resistance (MCR) model was used to simulate the trend of resource flows under conventional spillover effects and construct the regional food ecosystem service flow pattern. Then, based on the supply–demand matching dimension using the Bayesian belief network, the optimization areas were identified, and the corresponding optimization strategies were proposed. The results showed the following: (1) the spatial heterogeneity of regional food ecosystem services supply and demand was strong. The supply areas were widely distributed in the western and northern regions, while the demand areas were clustered in the eastern and southern coastal regions. (2) The flow pattern of regional food ecosystem services was mainly composed of 187 service flows centered around the Pudong New Area and other places, with flows ranging from 1,134 to 20,000 t. Shanghai, Hangzhou, and Nanjing were the main inflows, while Nantong and Xuancheng emerged as important outflows of food ecosystem services. Additionally, Zhejiang Province had the most frequent internal movements, while Jiangsu Province had the largest flow of food ecosystem services. (3) From the perspective of matching supply and demand, there were obvious spatial differences between important optimization areas and sub-optimization areas. The former was concentrated in the southern region, while the latter was continuously distributed in the western part of the study area. In the future, regional production potential should be further explored to enhance the supply capacity of food ecosystem services. The research methodology can effectively portray regional food ecosystem service flow patterns and identify priority areas for optimization, which can provide scientific guidance for ecosystem service management and food security.